Exploring English Language Teachers’ Motivation for teaching in Private Schools: A Narrative Analysis - Silwal, Gokul (Jana Adarsha Research Journal, 2025)
This study is an attempt to explore the existing motivating and demotivating factors in private schools in promoting teaching. Four English language teachers teaching in private schools were selected as a sample using a purposive non-random sampling procedure from Chitwan district. This is a narrative inquiry research design in which I applied in-depth interview as a tool to collect the required data to address the research objectives of this study. Using interpretive research paradigm, I analyzed and interpreted the data of the study. This study was conducted to find out the actual state of motivating and demotivating factors of private schools in promoting teaching of English language teachers. The findings of the study showed that remuneration and salary, institutional environment, recognition and prestige, flexible working hours, colleagues, and students, etc., have motivated the English language teachers for teaching in private schools whereas inadequate salary, tough working conditions and demanding work, not being participated in decision making process, lack of appreciation and motivation, etc., are demotivating them in teaching in private schools. This study will help private school principals, and administrators to make policy regarding teacher retention and motivation in their institutions and the aspiring English language teachers to seek their career in teaching in such institutions.